Disability in Patients with Inflammatory Bowel Disease: Correlations with Quality of Life and Patient's Characteristics. (29th May 2017) - Argyriou, Konstantinos; Kapsoritakis, Andreas; Oikonomou, Konstantinos; Manolakis, Anastassios; Tsakiridou, Eirini; Potamianos, Spyridon
Abstract : Background . Inflammatory bowel diseases may cause significant disability. However, little is known regarding the life domains where patients encounter most limitations. Objectives . To assess patients' overall disability and determine the life domains where most restrictions were applied. Secondarily, we sought for possible relationships among disability, quality of life (HRQoL), and population characteristics. Method . The study lasted for two years (2013–2015) and included 200 patients [ 52 % u l c e r a t i v e c o l i t i s ( U C ) ] from a referral centre. Disability was evaluated using the 36-item version of WHODAS 2.0 questionnaire. The influence of population characteristics on overall disability was assessed with linear regression. Results . Crohn's disease (CD) patients showed greater overall disability compared to UC (19.22 versus 15.01, p = 0.001 ), with higher scores in the domains of relationships, life activities, and participation. Disability was negatively associated with HRQoL (p < 0.001 ). Long activity, extensive disease, rural residence, and employment independently influenced the overall disability in both groups. Additionally, significant influence was recorded for lower education in the UC and for operation and celibacy in the CD group. Conclusions . CD patients were facing more limitations compared to those with UC, especially in the domains of relationships, activities, and participation. Other than clinical factors, sociodemographic characteristics were also associated with increased disability.